108k views
3 votes
Prove the following by induction. In each case, n is apositive integer.

2^n ≤ 2^n+1 - 2^n-1 -1.

User Yeray Diaz
by
5.9k points

2 Answers

4 votes

Answer:

We rewrite the inequality as follows:


2^n \leq 2^(n+1) - 2^(n-1) - 1\\1 \leq 2^(n+1) - 2^(n) - 2^(n-1)\\1 \leq 4\cdot 2^(n-2) - 2 \cdot 2^(n-1) - 2^(n-1)\\1 \leq (4-2-1) \cdot 2^(n-2)\\1 \leq 2^(n-2)

Which is true because n was given to be a positive integer.

User XDragonZ
by
5.6k points
1 vote

Answer with explanation:

We are asked to prove by the method of mathematical induction that:


2^n\leq 2^(n+1)-2^(n-1)-1

where n is a positive integer.

  • Let us take n=1

then we have:


2^1\leq 2^(1+1)-2^(1-1)-1\\\\i.e.\\\\2\leq 2^2-2^(0)-1\\\\i.e.\\2\leq 4-1-1\\\\i.e.\\\\2\leq 4-2\\\\i.e.\\\\2\leq 2

Hence, the result is true for n=1.

  • Let us assume that the result is true for n=k

i.e.


2^k\leq 2^(k+1)-2^(k-1)-1

  • Now, we have to prove the result for n=k+1

i.e.

To prove:
2^(k+1)\leq 2^((k+1)+1)-2^((k+1)-1)-1

Let us take n=k+1

Hence, we have:


2^(k+1)=2^k\cdot 2\\\\i.e.\\\\2^(k+1)\leq 2\cdot (2^(k+1)-2^(k-1)-1)

( Since, the result was true for n=k )

Hence, we have:


2^(k+1)\leq 2^(k+1)\cdot 2-2^(k-1)\cdot 2-2\cdot 1\\\\i.e.\\\\2^(k+1)\leq 2^((k+1)+1)-2^(k-1+1)-2\\\\i.e.\\\\2^(k+1)\leq 2^((k+1)+1)-2^((k+1)-1)-2

Also, we know that:


-2<-1\\\\i.e.\\\\2^((k+1)+1)-2^((k+1)-1)-2<2^((k+1)+1)-2^((k+1)-1)-1

(

Since, for n=k+1 being a positive integer we have:


2^((k+1)+1)-2^((k+1)-1)>0 )

Hence, we have finally,


2^(k+1)\leq 2^((k+1)+1)-2^((k+1)-1)-1

Hence, the result holds true for n=k+1

Hence, we may infer that the result is true for all n belonging to positive integer.

i.e.


2^n\leq 2^(n+1)-2^(n-1)-1 where n is a positive integer.

User Aniston
by
5.9k points